PLGA nanoparticles as an efficient carrier in Toxoplasma GAP45: a more effective vaccine against acute toxoplasmosis than traditional ones - Zhou, Pan; Yu, YanLi; Qi, WeiYu; Wang, XiaoJuan; Yu, YouLi; Wang, JianDong; Zhang, Li; Yu, ZhengQing; Liu, TingLi (Frontiers in Immunology, 2025)
IntroductionToxoplasma gondii (T. gondii), as a strict intracellular parasite, can infect nearly all mammals, including humans, posing significant threats to public health. Toxoplasmosis in animals also leads to substantial economic losses in animal husbandry. Currently, no effective treatments are available for toxoplasmosis, creating an urgent need for safe and efficient therapeutics.MethodsIn this study, we constructed a subunit vaccine using T. gondii glidesome-associated protein 45 (TgGAP45). To enhance immunogenicity, poly (lactic-co-glycolic acid) (PLGA) nanoparticles were employed as delivery carriers to prepare TgGAP45-PLGA nanospheres. For comparison, two oil adjuvants, Montanide™ ISA 660 VG and Montanide™ ISA 206 VG, were used to formulate TgGAP45-206VG and TgGAP45-660VG emulsions. Following safety evaluation, protective immunity was assessed in animals. Antibody levels, cytokine profiles, dendritic cell (DC) maturation and differentiation, and T lymphocyte proliferation and differentiation were analyzed.ResultsThe results demonstrated that TgGAP45-PLGA nanospheres induced a mixed Th1/Th2 immune response against T. gondii. Furthermore, parasite burden analysis in spleen and heart tissues revealed that TgGAP45-PLGA nanospheres provided the strongest immunoprotection among the tested vaccines.DiscussionThese findings indicate that TgGAP45 delivered via PLGA nanospheres is a promising candidate for preventing acute toxoplasmosis. Further studies and applications are warranted to explore its full therapeutic potential.